Psychosocial Adaptation Model on Tuberculosis Clients Using Uncertainty in Illness Theory Approach in Jember - Anita Fatarona; Soedarsono Soedarsono; Laily Hidayati (Jurnal Kesehatan dr. Soebandi, 2022)
ABSTRACT Introduction: Pulmonary tuberculosis is an infectious disease that has a psychosocial impact on the sufferer. The government program, is still applicable to the treatment and transmission of disease. Objective: This study was to structural models of psychosocial adaptation in patients with tuberculosis (TB) who underwent treatment using the theory of uncertainty in the disease at Jember Health Centre. Methods: The research is included in the explanative survey method using a cross sectional approach. Samples were taken according to the inclusion criteria of 100 respondents. Sampling using simple random sampling technique. The independent variables in this study, among other: sex, age, marital status, duration of treatment, knowledge, expectations, ethnicity, stigma, occupation, family support, communication, education, uncertainty, coping and psychosocial adaptation. Data were collected using structured questionnaires and analyzed using Partial Least Square (PLS). Results: The result of the research showed that: cognitive factor gave significant effect to uncertainty (t statistic 2,686 >1,6), psychological factor did not give significant effect to uncertainty(t statistic 0, 418 <1,6), social factor gave significant influence to uncertainty (t statistic 7, 496 >1,6), factor uncertainty has a significant effect on coping(t statistic 5,572 >1,6), Coping factors have an effect on psychosocial adaptation(t statistic 7, 911 >1,6). This study cognitive knowledge has a direct influence on uncertainty. uncertainty decreases because the knowledge of TB clients increases. TB clients understanding of the information provided by health workers can reduce the worries and confusion. Conclusion: This psychosocial adaptation nursing model has good predictive relevance.